HUBUNGAN MEKANISME KOPING DENGAN STRES KERJA PERAWAT DI RSU GMIM BETHESDA TOMOHON - Mundung, Grace Jinny; Kairupan, B H Ralph; Kundre, Rina (Universitas Sam Ratulangi, 2019)
Abstract :Stress is an epidemic that spreads throughout the world according to the WorldHealth Organization. Stress occurs in Asian countries Survey from PPNI in 2006, around50.9% of nurses, worked in 4 provinces in Indonesia. Objective :this research is to know thecorrelation between coping mechanisms with job stress in nurses at general hospital GMIMBethesda Tomohon. Research Design : Type of this research is quantitative and usingdescriptive analytic research method with cross sectional approach. The sampling techniqueusing probability sampling, stratified random sampling method and to determine the samplesize, using the Slovin formula and obtained a sample of 53 respondents. Research Result :This research used the Kolmogorov-Smirnov test at a significant level of 95% which foundthat a significant value was 0.001. Conclusion : results of this research indicate that there isa correlation between coping mechanisms and job stress in nurses at general hospital GMIMBethesda Tomohon.Keywords: Nurse, Coping Mechanisms, Job StressAbstrak :Menurut World Health Organization stres merupakan epidemi yang menyebar keseluruh dunia. Stres terjadi di negara-negara Asia. Survei dari PPNI tahun 2006, sekitar50,9% perawat yang bekerja di 4 provinsi di Indonesia mengalami stres kerja. Tujuan :penelitian ini bertujuan untuk mengetahui hubungan mekanisme koping dengan stres kerjaperawat di RSU GMIM Bethesda Tomohon. Desain penelitian : jenis penelitian kuantitatifmenggunakan metode penelitian deskriptif analitik dengan pendekatan cross sectional.Teknik pengambilan sampel probability sampling metode stratified random sampling danuntuk menentukan besar sampel menggunakan rumus Slovin, didapat jumlah sampelsebanyak 53 responden. Hasil penelitian : menggunakan uji Kolmogorov-smirnov padatingkat kemaknaaan 95% di dapat bahwa nilai signifikan adalah 0.001. Kesimpulan : hasilpenelitian ini menunjukkan terdapat hubungan antara mekanisme koping dengan stres kerjaperawat di RSU GMIM Bethesda Tomohon.Kata Kunci: Perawat, Mekanisme Koping, Stres Kerja